2006
DOI: 10.1021/bi061788m
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the PheA Domain of Gramicidin Synthetase Leads to a New Understanding of the Enzyme's Mechanism and Selectivity

Abstract: The PheA domain of gramicidin synthetase A, a non-ribosomal peptide synthetase, selectively binds phenylalanine along with ATP and Mg2+ and catalyzes the formation of an aminoacyl adenylate. In this study, we have used a novel protein redesign algorithm, K*, to predict mutations in PheA that should exhibit improved binding for tyrosine. Interestingly, the introduction of two predicted mutations to PheA did not significantly improve KD, as measured by equilibrium fluorescence quenching. However, the mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 19 publications
3
62
0
Order By: Relevance
“…Luo et al (30) claimed that the discrimination of the amino acid substrate begins when the transition state is formed during the catalysis. Stevens et al (3) suggested that a conformational change toward a catalytically relevant intermediate occurs in the adenylation process of PheA. In our results, the double mutant T278L/A301G dramatically lowers the value of K m for the noncognate amino acid Leu from the WT PheA, requiring changes to only two residues in the active site.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Luo et al (30) claimed that the discrimination of the amino acid substrate begins when the transition state is formed during the catalysis. Stevens et al (3) suggested that a conformational change toward a catalytically relevant intermediate occurs in the adenylation process of PheA. In our results, the double mutant T278L/A301G dramatically lowers the value of K m for the noncognate amino acid Leu from the WT PheA, requiring changes to only two residues in the active site.…”
Section: Discussionsupporting
confidence: 47%
“…Several studies have shown that the substrate specificity of the adenylation domain can be modified by the mutation of the active-site residues (3,24,31). By using a multiple sequence alignment approach to redesign the substrate specificity of GrsA-PheA, Stachelhaus et al (24) successfully improved the activity of the enzyme for the noncognate amino acid Leu with the introduction of a double mutation, T278M/A301G, and altered the substrate specificity of an aspartate-activating domain AspA to Asn by a single mutation H322E in the active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protein design algorithms have successfully predicted protein sequences that fold and bind the desired target in vitro (Frey et al, 2010;Roberts et al, 2012;Rudicell et al, 2014;Stevens et al, 2006;Georgiev et al, 2012;Georgiev and Donald, 2007;Georgiev et al, 2014;Donald, 2011), and even in vivo (Reeve et al, 2015;Roberts et al, 2012;Rudicell et al, 2014;Georgiev et al, 2012;Georgiev et al, 2014;Donald, 2011). However, protein design is NP-hard (Kingsford et al, 2005), making algorithms that guarantee optimality expensive for larger designs where many residues are allowed to mutate simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…By explicitly modeling proteins as a thermodynamic ensemble of molecular conformations, osprey/K* has successfully designed sequences that have performed well both in vitro Chen et al, 2009;Frey et al, 2010;Rudicell et al, 2014;Georgiev et al, 2012;Gorczynski et al, 2007;Stevens et al, 2006) and in vivo Gorczynski et al, 2007;Rudicell et al, 2014;Frey et al, 2010), as well as in non-human primates . K* accomplishes this by using dead end elimination followed by A* (DEE/A*) (Leach and Lemon, 1998;Goldstein, 1994) to provably compute a gap-free list of conformations within an energy window E w of the GMEC, and provably approximate partition functions over molecular ensembles.…”
Section: Introductionmentioning
confidence: 99%